Community Participation in Rural Development: A Case for Environmental Assessment. (2000)
In the face of the popularity of sustainable development, rural development must have an environmentally - friendly posture-thus the need for environmental assessment of proposed projects. This paper makes a case for community participation in environmental assessment addressing the obvious advantages therein. It asserts that the low level of community participation in environmental assessment may have a negative effect on the effectiveness of the performance of the project. It finally makes a call for proper legislation that will give the community a greater and higher level of participation in environmental assessment.